"Ownership structure and firm performance: the mediating role of board characteristics". Issue 4 (5th May 2020) - Rashid, Md Mamunur
Abstract : Purpose: The purpose of this study is to examine the mediating role of corporate board characteristics in the relationship between ownership structure and firm performance in the listed public limited companies of Bangladesh. Design/methodology/approach: The study analyzed 527 annual reports of listed companies in Bangladesh for the years 2015-2017. The direct and indirect effect of ownership structure on firm performance was examined using AMOS 23. Baron and Kenny's (1986) four steps procedure was used to establish the mediating role of board characteristics. Findings: The results demonstrated that foreign ownership and director ownership have significant positive influence on both accounting and market based firm's performance, while institutional ownership exhibits positive influence only on accounting-based performance (return on assets). With respect to mediating effect, the results show that board size and board independence partially mediate the relationship between ownership structure and firm performance. Research limitations/implications: The major limitation of the study is that it focuses only on three years data in examining the hypothesized relationship among the variables. Practical implications: Investors, regulators and managers can get evocative insights, particularly who seek to improve their company's performance in the capital market through restructuring their ownership structure and board composition. Originality/value: The study focuses on both direct and indirect effect of ownership structure on firm performance in the context of an emerging and developing economy. In examining the indirect effect, the study uses board size and board independence as the mediating variables.